Aflatoxin Toxicity Reduction in Feed by Enhanced Binding to Surface-Modified Clay Additives - Richard E. Zartman; William F. Jaynes (Toxins, 2011)
Animal feeding studies have demonstrated that clay additives, such as bentonites, can bind aflatoxins in ingested feed and reduce or eliminate the toxicity. Bentonite deposits are found throughout the world and mostly consist of expandable smectite minerals, such as montmorillonite. The surfaces of smectite minerals can be treated with organic compounds to create surface-modified clays that more readily bind some contaminants than the untreated clay. Montmorillonites treated with organic cations, such as hexadecyltrimethylammonium (HDTMA) and phenyltrimethylammonium (PTMA), more effectively remove organic contaminants, such as benzene and toluene, from water than untreated clay. Similarly, montmorillonite treated with PTMA (Kd = 24,100) retained more aflatoxin B1 (AfB1) from aqueous corn flour than untreated montmorillonite (Kd = 944). Feed additives that reduced aflatoxin toxicity in animal feeding studies adsorbed more AfB1 from aqueous corn flour than feed additives that were less effective. The organic cations HDTMA and PTMA are considered toxic and would not be suitable for clay additives used in feed or food, but other non-toxic or nutrient compounds can be used to prepare surface-modified clays. Montmorillonite (SWy) treated with choline (Kd = 13,800) and carnitine (Kd = 3960) adsorbed much more AfB1 from aqueous corn flour than the untreated clay (Kd = 944). A choline-treated clay prepared from a reduced-charge, high-charge montmorillonite (Kd = 20,100) adsorbed more AfB1 than the choline-treated high-charge montmorillonite (Kd = 1340) or the untreated montmorillonite (Kd = 293). Surface-modified clay additives prepared using low-charge smectites and nutrient or non-toxic organic compounds might be used to more effectively bind aflatoxins in contaminated feed or food and prevent toxicity.